Two-Bubble Acoustic Tweezing Cytometry for Biomechanical Probing and Stimulation of Cells - Chen, Di (Biophys J, 2015)
The study of mechanotransduction relies on tools that are capable of applying mechanical forces to elicit and assess cellular responses. Here we report a new (to our knowledge) technique, called two-bubble acoustic tweezing cytometry (TB-ATC), for generating spatiotemporally controlled subcellular mechanical forces on live cells by acoustic actuation of paired microbubbles targeted to the cell adhesion receptor integrin. By measuring the ultrasound-induced activities of cell-bound microbubbles and the actin cytoskeleton contractile force responses, we determine that TB-ATC elicits mechanoresponsive cellular changes via cyclic, paired displacements of integrin-bound microbubbles driven by the attractive secondary acoustic radiation force (sARF) between the bubbles in an ultrasound field. We demonstrate the feasibility of dual-mode TB-ATC for both subcellular probing and mechanical stimulation. By exploiting the robust and unique interaction of ultrasound with microbubbles, TB-ATC provides distinct advantages for experimentation and quantification of applied forces and cellular responses for biomechanical probing and stimulation of cells.